Health Classification and Its Effect on the Performance of College Students - Endozo, Dr. Anatalia N.; Oluyinka, Dr. Solomon (IJRDO- Journal of Educational Research, 2019)
It is a known fact physical activity performance improves health. Not just does it improve circulation, increment blood stream to the mind, and raise endorphin levels, which all assist to diminish pressure, improve temperament and mentality. Physically dynamic students may likewise accomplish all the more scholastically. According to Reilly (2015) physically fit students are more averse to miss school, share in unsafe practices, get pregnant, or endeavor suicide, which are altogether connected with better results in school. Several studies have demonstrated the positive effects of physical education and physical activity on school performance. Increased time for physical activity can lead to better concentration, reduced disruptive behaviors and higher test scores in reading, math and writing (Galla & Duckworth , 2015).